Policy insights for national school meals programmes: Annual Research Statements to the members of the School Meals Coalition - 2022, 2023, and 2024 - , Research Consortium for School Health; Nutrition; Bundy, Donald A.P.; Schultz, Linda; Morris, Kate; Catmull, Jasmine; Crowley, Georgia; Vickers, Sarah; Eustachio Colombo, Patricia; Osman, Muna; Miki, Gilbert; Makumbe, Edward; et al. (Frontiers in Public Health, 2025)
The scale and near universality of school closures in response to the COVID-19 pandemic highlighted the vital role schools play in protecting the health and wellbeing of learners. This experience strengthened the resolve of countries to re-establish and increase their investment in the education and wellbeing of children as part of building back from the pandemic, resulting in the creation of a global School Meals Coalition (SMC) to help achieve that ambition by 2030. The Research Consortium for School Health and Nutrition was launched in 2021 to provide independent, evidence-based guidance on effective policymaking on school health and nutrition programming to the (now) 109 member states of the Coalition. Guided by a 10-year independent research strategy, the Research Consortium operates as a global network of academics and scholars and consolidates research findings into policy insights that offer actionable approaches to strengthen the quality, efficiency, and coverage of national programmes. With input from over 1,200 Global Academy members from more than 110 countries, the Research Consortium develops an Annual Research Statement on the policy implications of the emerging research in this area, which is presented to policymakers annually at a global convening of the SMC member states. This paper introduces the Research Consortium’s Annual Research Statements for years 2022, 2023, and 2024, which report new programmatic and policy insights as well as accumulating and evolving understanding of the research on school health and nutrition.